Internal control and fraud in construction industry of Malaysia / Wan Noor Asmuni Wan Fauzi,Siti Haliza Asat and Junaidah Hanim Ahmad - Wan Fauzi, Wan Noor Asmuni; Asat, Siti Haliza; Ahmad, Junaidah Hanim (Universiti Teknologi MARA Kelantan, 2019)
The purpose of this paper is to develop an understanding about the internal control and fraud problem in the Malaysian construction industry. It is believed that the construction industry is one of the riskiest industries regarding internal fraud due to its complex and costly nature, and dense third-party contract relationships. If this situation is left untreated, it will lead to more serious problems in the future of construction industry in Malaysia. Therefore, this study is aimed to discuss the fraud phenomenon, lack of internal control and the reasons behind fraud in construction industry. It also proposes that organizations should periodically perform formal risk assessments and internal control reviews to reduce fraud activities. It is recommended to all parties to promote and practice effective internal control in their project to minimize the occurrence of fraud and failures.